Deceptive (De)humanization: How Lying About Perceived Outgroups is Revealed in Language. (March 2023) - Markowitz, David M.
This paper introduces the concept of deceptive (de)humanization, the internal belief that an outgroup is less-than-human while dishonestly acknowledging aspects of their humanity for impression management purposes. In a large online experiment ( N = 1, 169), participants wrote about their false or truthful opinions on an outgroup they perceived as more evolved or less evolved. Following several automated text analyses, the data indicated psychological differences in attention through word patterns. Consistent with prior work, deceptive texts contained fewer self-references and more negative emotion terms than truthful texts, and dehumanizers used more negative emotions than humanizers. New evidence suggests those who wrote deceptively about evolved groups focused the most on negative emotions compared to other participants. This work extends deception and dehumanization theory by investigating how such psychological constructs interact, and how they are reflected linguistically as communicators attempt to manage impressions and maintain a positive self-image.